Increasing temperature and prey availability affect the growth and swimming kinematics of Atlantic herring (Clupea harengus) larvae. (2nd April 2022) - Allan, Bridie J M; Browman, Howard I; Shema, Steven; Skiftesvik, Anne-Berit; Folkvord, Arild; Durif, Caroline M F; Kjesbu, Olav Sigurd
Abstract: Climate change will increase the magnitude and duration of warming events and the variability in the phenology and abundance of available prey to the early life stages of fish. These factors influence physiological, behavioral and ecological processes, impacting growth, development and survival. Using a fully factorial design with two prey-availability treatments (1200 prey items L −1 (high prey abundance) or 40 prey items L −1 (low prey abundance)) under three temperature regimes (8, 10 and 12°C), the swimming kinematics of 6-week old spring-spawning Atlantic herring larvae were examined using silhouette video photography. Higher temperatures combined with food limitation significantly decreased the growth and swimming kinematics of larval herring, with the most negative effect observed in larvae reared at 12°C and exposed to low food abundances. Specifically, larvae displayed reduced locomotory behaviors and reduced vertical movements. By contrast, larvae reared at high prey abundance and at 12°C displayed more active swimming and exploratory behavior, as evidenced by an increase in both locomotory behavior and vertical and horizontal turn angles, suggesting increased motivation to search for food. This research highlights the importance of determining to what degree fish larvae are sensitive to changes in temperature and how these changes might be further influenced by food availability.